2016
DOI: 10.21831/jsd.v4i2.9090
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Biodegrdable Plastic From Casava Starch and Aloe Vera Extract With Glycerol Plasticizer

Abstract: AbstrakSintesis dan karakterisasi plastik biodegradable dari pati onggok singkong, gliserol, asam asetat dan ekstrak lidah buaya telah dilakukan. Penelitian bertujuan untuk mengetahui pengaruh penambahan ekstrak lidah buaya terhadap sifat mekanik, laju transmisi uap air serta biodegradasi plastik. Terdapat lima tahapan utama dalam penelitian yaitu pembuatan ekstrak lidah buaya, pembuatan pati dari onggok singkong, pembuatan plastik biodegradable, karakterisasi plastik biodegradable dan uji biodegradasi plastik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…The greater the concentration of modified starch, the more modified starch is formed so that the mechanical properties of bioplastics are stronger and difficult to break because it requires a large amount of energy to break it, therefore increasing the concentration of modified starch will increase the tensile strength of bioplastics. This is supported by Apriyani and Sedy (2015) who state that the addition of starch concentration will bind more hydrogen, making it difficult to break [12]. The hydrogen bonds formed to cause the film to become less flexible and become hard.…”
Section: Discussionmentioning
confidence: 86%
“…The greater the concentration of modified starch, the more modified starch is formed so that the mechanical properties of bioplastics are stronger and difficult to break because it requires a large amount of energy to break it, therefore increasing the concentration of modified starch will increase the tensile strength of bioplastics. This is supported by Apriyani and Sedy (2015) who state that the addition of starch concentration will bind more hydrogen, making it difficult to break [12]. The hydrogen bonds formed to cause the film to become less flexible and become hard.…”
Section: Discussionmentioning
confidence: 86%
“…Plastic samples are tested for 7 hours and weighed every 1 hour (from 0 to 7 hours). Weight gain indicates how much speed of diffusion water vapor passes through the plastic [16] . The water vapor transfer rate g/m 2 /hour is calculated using the following formula:…”
Section: Water Vapor Transfer Ratementioning
confidence: 99%
“…The addition of glycerol resulted in the large number of OH groups it had, so it was very possible for the edible film to bind with water and result in a change in the location of the functional groups [24]. The occurrence of this kind of wave number-shifting process indicated a polymerization reaction of biodegradable plastic materials during blending [25]. Based on the results of the FTIR test above, it showed that there are new functional groups, this was because the addition of plasticizer resulted in edible films occurring chemically.…”
Section: Functional Groups (Ftir)mentioning
confidence: 99%